2010
DOI: 10.1007/s11806-010-0019-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic geometry monitoring system and its application in Sutong Bridge construction

Abstract: The construction period of large cable-stayed bridges is long, and the structure deformation is complicated. Any error during construction will potentially affect the cantilever alignments and the internal forces. In order to ensure safety during construction and exactly determine the cantilever alignments, dynamic deformation monitoring is needed immediately when the construction of the superstructure starts. This paper aims at the requirement of deformation monitoring during the Sutong Bridge construction, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…It can be seen from Table 1 that the accuracy obtained from one and five minutes is better than ±4 mm in both directions. Compared with the results obtained from ten minutes and one hour, the mean square error decreases with smaller data intervals and this complies with that of Zhang et al [26]. Therefore, the results indicated that the GPS positioning accuracy is better than ±6 mm; in addition, this accuracy is acceptable to measure the semistatic and dynamic performances of the towers.…”
Section: Gps Measurement Accuracy Assessmentsupporting
confidence: 87%
See 1 more Smart Citation
“…It can be seen from Table 1 that the accuracy obtained from one and five minutes is better than ±4 mm in both directions. Compared with the results obtained from ten minutes and one hour, the mean square error decreases with smaller data intervals and this complies with that of Zhang et al [26]. Therefore, the results indicated that the GPS positioning accuracy is better than ±6 mm; in addition, this accuracy is acceptable to measure the semistatic and dynamic performances of the towers.…”
Section: Gps Measurement Accuracy Assessmentsupporting
confidence: 87%
“…Zhang et al [26] estimated the measurement accuracy of monitoring GPS system based on statistical analysis for two days. Therefore, in this study, two days monitoring data, 11 and 12 January 2008, are considered for the analysis of the dynamic performance of the towers.…”
Section: Gps Measurement Accuracy Assessmentmentioning
confidence: 99%
“…where ∀ means 'for any'; Equation (6) means that the value |Ψ f (τ, ϖ)| of a harmonic signal f (t) with frequency β could reach the local maximum at any point in time τ and only if the variable ϖ is equal to β, so we need to first determine ϖ; Equation (7) indicates that the local maximum can be regarded as the instantaneous amplitude when ϖ equals β, i.e., |Ψ f (τ, ϖ)| is exactly the harmonic signal itself. For another time point τ, repeating the steps yields the instantaneous frequency, phase, and amplitude [32].…”
Section: The Theory Of the 'Inaction Method'mentioning
confidence: 99%
“…However, the diversification of bridge structures and the continuous increase in span lengths have presented greater challenges in bridge design, construction, and management. While promoting the development of related industries, ensuring the structural safety of bridges has become a crucial concern for construction managers [11][12][13]. Ensuring structural safety has become an indispensable part of the bridge construction process.…”
Section: Introductionmentioning
confidence: 99%